Implementasi Dan Pengujian Sistem Informasi Jasa Penyewaan Kendaraan Bermotor Menggunakan Standar ISO 9126 Studi Kasus : PT. XYZ - Agus Umar Hamdani (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
PT. XYZ is a service company enganged in motor vehicle rental services. Over time, it business give a good prospect for the future. Competition between companies is very increasingly and development of technology information is very rapidly become a challenge and a great benefit to the company’s business activities. Companies need to take advantage of developments in information technology to improve business performance, quality of data and information to increase the number of customers. Therefore, this reseach tries to answer how make a model of information system for motor vehicle rental services that can help to provide optimum services. In this reseach, we use Object-Oriented Analysis and Design (OOAD) methodology for developing the proposed system, programming language use Microsoft Visual .Net 2008 and use MySQL for database systems, and Model ISO 9126 for testing system.